Incorporating Ubuntu principles in a tutor training programme to promote academic success and wellbeing - Mueletshedzi Ndwambi; Sipho Hlabane; Daniel Motlhabane; Antoinette Malgas (University of Johannesburg, 2022)
Tutoring is one of the important components of student support designed to enable students to achieve their learning goals and improve overall success rates. Due to the pandemic, the use of educational technologies has moved from being a secondary mode of conducting learning interactions in the tutoring space to being the primary mode of learning. A question worth asking is: "what does tutoring look like when most students are no longer on campuses?" In an online environment, tutors are not only expected to support students with their cognitive and academic skills but also need to offer support on other skills such as social, affective, technical and metacognitive skills. This requires a paradigm shift in the roles and responsibilities of tutors. This reflective paper reports on the Tutor Professional Learning Programme (TPLP) which identified Ubuntu as a principle that tutors can utilise to support students to develop a range of skills required to succeed in an online learning environment. Characteristics that are associated with Ubuntu include but are not limited to: being caring, humble, thoughtful, considerate, understanding, wise, generous, hospitable, socially mature, socially sensitive and virtuous. These are identified as desirable characteristics that online tutors should possess.